2018
DOI: 10.1002/clc.22925
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2‐VASc score and clinical outcomes of patients with chest pain discharged from internal medicine wards following acute coronary syndrome rule‐out

Abstract: Background Chest‐pain patients deemed safe for discharge from internal medicine wards might still be at risk for adverse outcomes. Hypothesis CHA2DS2‐VASc score improves risk stratification of low‐risk chest‐pain patients discharged after acute coronary syndrome (ACS) rule‐out. Methods We accessed medical records of patients who were admitted to internal medicine wards at a single medical center during 2010–2016 and discharged following an ACS rule‐out. Patients were classified according to CHA2DS2‐VASc score:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The CHA 2 DS 2 -VASc score [congestive heart failure, hypertension, age ≥75 years (doubled), diabetes, stroke/transient ischemic attack/thromboembolism (doubled), vascular disease (prior myocardial infarction, peripheral artery disease, or aortic plaque), age 65-74 years, sex category (female)] has been used for the assessment of thromboembolic (TE) risk and the guidance of antithrombotic treatment in patients with AF (20). In addition, this simple and well-established scoring system has been shown to predict the risk for other conditions beyond its original designations (20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…The CHA 2 DS 2 -VASc score [congestive heart failure, hypertension, age ≥75 years (doubled), diabetes, stroke/transient ischemic attack/thromboembolism (doubled), vascular disease (prior myocardial infarction, peripheral artery disease, or aortic plaque), age 65-74 years, sex category (female)] has been used for the assessment of thromboembolic (TE) risk and the guidance of antithrombotic treatment in patients with AF (20). In addition, this simple and well-established scoring system has been shown to predict the risk for other conditions beyond its original designations (20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…High CHA 2 DS 2 -VASc score is associated with worse long term outcomes in patients with coronary disease, 16 acute coronary syndrome, 6 and even in patients who were evaluated for chest pain. 5 It is reasonable to assume that CHA 2 DS 2 -VASc score is valuable in HF, because its components are prognostic factors in HF. 17 There are limited data available regarding the CHA 2 DS 2 -VASc score in predicting HF outcomes in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CHA 2 DS 2 ‐VASc score is recommended for the assessment of the risk of thromboembolic event in patients with AF, in recent years, it is used to predict outcomes in several other cardiovascular diseases. High CHA 2 DS 2 ‐VASc score is associated with worse long term outcomes in patients with coronary disease, 16 acute coronary syndrome, 6 and even in patients who were evaluated for chest pain 5 . It is reasonable to assume that CHA 2 DS 2 ‐VASc score is valuable in HF, because its components are prognostic factors in HF 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the CHA2DS2-VASc score include congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, prior stroke or transient ischemic attack (TIA) or thromboembolism, vascular disease, age 65–74 years, and sex category. Apart from the prediction of the risk of stroke, recent studies have shown an association between the score and outcome of acute myocardial infarction, stroke, and chest pain [ 14 , 15 , 16 ]. The CHA2DS2-VASc score is simple to apply in clinical practice.…”
Section: Introductionmentioning
confidence: 99%